A biomass estimation of epifaunal megabenthos by stereophotography around Syowa Station, Antarctica - Numanami, Hideki; Hamada, Etsuyuki; Naito, Yasuhiko; Taniguchi, Akira (1986)
P(論文) Biomass estimation of epifaunal megabenthos was made with stereographic photographs which were taken at four stations in the Syowa Station area, Antarctica, in January 1984. The size of individuals was measured with reading of photographs and then it was converted into the wet weight based on the size-weight relationship for each species. The values of the equilibrium constant and the initial growth index were computed for the direct measurement of size and weight of preserved samples. The total biomass estimated at the station of 16m in depth in the Kita-no-seto Strait, the stations of 40 and 80m in depth in the Kita-no-ura Cove and the station of 200m in depth in the Ongul Strait was 791±138,2834±655,1984±492 and 423±110g/m^2,respectively. These were considered reasonable figures for the epifaunal megabenthos in the Antarctic coastal waters. Application of underwater stereophotography is considered to be one of the effective methods for the biomass estimation of epifaunal megabenthos. departmental bulletin paper